Effect of Culture Conditions on Phytase Production by Aspergillus ficuum in Solid-state Fermentation Using Rice Bran as Substrate - Kusharyoto, Wien; Sari, Martha; Ridwanuloh, Asep Muhamad (Annales Bogorienses, 2009)
Phytic acid is an antinutritional factor that forms 1–2% of most of the seeds and their co-products representing more than 60% of their total phosphorus. Monogastric and agastric animals are unable to utilize phytate phosphorus either due to lack of or insufficient amount of phytate degrading enzymes. Phytases (myo-inositol hexakisphosphate-phosphohydrolase) are a special class of phosphatases that catalyze the hydrolysis of phytic acid in a stepwise manner to lower inositol phosphates, myo-inositol and inorganic phosphate. Phytases are found naturally in plants and microorganisms and a sizeable number of phytases have been purified and characterized from various fungi, yeasts, and bacteria. The present investigation involves studies on the effect of moisture content, pH value and different media ingredients such as carbon, nitrogen, and surfactants on the production of phytase by the fungus Aspergillus ficuum DSM 932 in solid-state fermentation (SSF) using rice bran as substrate. The production of phytase by SSF was favored, when the fungus was grown at a moisture content of 60% and pH 7.0, resulted in a phytase activity of 5.2 units/g dry substrate. There was a 20% increase in phytase yield in the presence of sucrose in SSF medium, while glucose and fructose were not effective in enhancing the phytase activity when used individually. Yeast extract was found to be a favorable nitrogen source for phytase production by SSF, which resulted in a 20% increase in phytase activity. There was no significant effect in increasing phytase production with the use of either soy peptone or tryptic soy as nitrogen source. Approximately 30% inhibition in phytase activity was shown in the presence of the surfactant Tween-80 or Triton X-100 in the SSF. By supplementing rice bran with sucrose and yeast extract, and performing the SSF in tray bioreactors, a phytase activity of 6.76 units/g dry substrate could be obtained.